Highly efficient hairy root genetic transformation and applications in citrus - Ma, Haijie; Meng, Xinyue; Xu, Kai; Li, Min; Gmitter, Fred G.; Liu, Ningge; Gai, Yunpeng; Huang, Suya; Wang, Min; Wang, Min; Wang, Nian; Xu, Hairen; et al. (Frontiers in Plant Science, 2022)
Highly efficient genetic transformation technology is greatly beneficial for crop gene function analysis and precision breeding. However, the most commonly used genetic transformation technology for woody plants, mediated by Agrobacterium tumefaciens, is time-consuming and inefficient, which limits its utility for gene function analysis. In this study, a simple, universal, and highly efficient genetic transformation technology mediated by A. rhizogenes K599 is described. This technology can be applied to multiple citrus genotypes, and only 2–8 weeks were required for the entire workflow. Genome-editing experiments were simultaneously conducted using 11 plasmids targeting different genomic positions and all corresponding transformants with the target knocked out were obtained, indicating that A. rhizogenes-mediated genome editing was highly efficient. In addition, the technology is advantageous for investigation of specific genes (such as ACD2) for obtaining “hard-to-get” transgenic root tissue. Furthermore, A. rhizogenes can be used for direct viral vector inoculation on citrus bypassing the requirement for virion enrichment in tobacco, which facilitates virus-induced gene silencing and virus-mediated gene expression. In summary, we established a highly efficient genetic transformation technology bypassing tissue culture in citrus that can be used for genome editing, gene overexpression, and virus-mediated gene function analysis. We anticipate that by reducing the cost, required workload, experimental period, and other technical obstacles, this genetic transformation technology will be a valuable tool for routine investigation of endogenous and exogenous genes in citrus.